Field evaluation and safety management of ImPACT tough robotics challenge - Kimura, T.; Takamori, T.; Sheh, Raymond; Murao, Y.; Igarashi, H.; Hasumi, Y.; Houshi, T.; Tadokoro, S. (2019)
© Springer Nature Switzerland AG 2019. This chapter describes the development and the safety management of the facilities used in the field evaluation of the ImPACT Tough Robotics Challenge (TRC) in order to accelerate the technology and market innovation. Several evaluation fields have been developed in the TRC, e.g., a plant mock-up, a UAV evaluation facility, and a rubble field. In Sect. 10.1 (corresponding author: T. Takamori), the development of the rubble field is described. The other evaluation fields are developed almost in the same manner, and the experience and knowledge of the developments will be carried through to the development of Fukushima RTF, which will be opened in 2020 as one of the largest field evaluation facilities for the response robots in the world. In Sect. 10.2 (corresponding author: T. Kimura), the safety management associated with the rubble field is explained based on international safety standards. Two safety principles, the separation principle and the stop principle, are mainly used for risk reduction. In Sect. 10.3 (corresponding author: R. Sheh), the application of the Standard Test Method (STM) for response robots performance to the TRC is discussed for performing quantitative assessment of the robot performance. Related STMs for the TRC are introduced and Visual Acuity is identified as the most broadly relevant to all robots in the TRC. The new Automated Visual Acuity test method is introduced and described here. Each topic is written by the corresponding authors individually.